An Integrated Innovation DiffusionTrust-Building Framework for Understanding Mobile Payment Adoption in Indonesia’s Cross-Border Regions - Klaasvakumok J. Kamuri; Andrias U. T. Anabuni (Journal of Management and Business Innovation, 2025)
Mobile payment adoption in Indonesia has expanded rapidly; however, its diffusion in cross-border regions remains limited due to infrastructural inadequacies, heightened cross-border transaction risks, and low levels of trust in digital financial platforms. These regions—marked by high population mobility, informal economic activity, and uncertain regulatory oversight—create a unique context in which conventional technology adoption models may not fully capture user behaviour. This study introduces an integrated framework that combines Innovation Diffusion Theory and Trust-Building Theory to investigate how mobility, customization, security, and reputation shape trust and influence mobile payment adoption in Indonesia’s international border areas. The framework further examines the role of trust in mitigating perceived risk and strengthening continuance usage intention, while also assessing gender as a moderating variable. Data were obtained from 225 mobile payment users residing in major border gateways between Indonesia and Malaysia, Timor-Leste, and Papua New Guinea. Using partial least squares structural equation modelling (PLS-SEM), the results indicate that security, customization, and reputation significantly enhance trust, whereas mobility does not exert a meaningful effect within the border context. Trust substantially increases continuance usage intention and reduces perceived risk; however, perceived risk does not significantly influence continuance intention. Gender is also found to have no moderating effect on any of the hypothesized relationships. This study contributes to the mobile payment literature by providing a contextualized understanding of user behaviour in high-risk, infrastructure-constrained environments. It also offers practical implications for policymakers and fintech providers aiming to expand digital financial inclusion and strengthen trust-based payment ecosystems in Indonesia’s cross-border regions.